2009
DOI: 10.1089/dna.2009.0926
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Polymorphisms of Gene 8-Oxoguanine Glycosylase 1 and the Level of Oxidative DNA Damage in Peripheral Blood Lymphocytes of Patients with Alzheimer's Disease

Abstract: The purpose of this study was to determine the level of 8-oxo-2'-deoxyguanosine (8-oxo2dG) and expression of three isoforms of 8-oxoguanine glycosylase 1 (OGG1), OGG1-1a, 1b, and 1c, and OGG1 protein and Ser326Cys and Arg46Gln polymorphisms of the OGG1 gene, in peripheral blood lymphocytes of patients with Alzheimer's disease (AD) and healthy controls. The study was performed in 41 AD patients and 51 healthy subjects. The level of 8-oxo2dG was determined by high performance liquid chromatography/electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…MTH1 possesses the specific enzymatic activity necessary to convert the deleterious 8-oxoguanine-containing deoxyribonucleoside triphosphate into monophosphates, thus preventing its misincorporation into DNA and thereby minimizing the accumulation of oxidized DNA in neurons. Additionally, MTH1 activity is significantly decreased in AD subjects (28,29). Therefore, we examined the effect of MTH1 on estrogen-mediated DNA protection.…”
Section: Discussionmentioning
confidence: 97%
“…MTH1 possesses the specific enzymatic activity necessary to convert the deleterious 8-oxoguanine-containing deoxyribonucleoside triphosphate into monophosphates, thus preventing its misincorporation into DNA and thereby minimizing the accumulation of oxidized DNA in neurons. Additionally, MTH1 activity is significantly decreased in AD subjects (28,29). Therefore, we examined the effect of MTH1 on estrogen-mediated DNA protection.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we focused on the variants of the OGG1 gene that had previously been investigated for breast cancer, bladder cancer, and Alzheimer's disease [24][25][26]. We found a statistically significant association between the RA and the rs3219008 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found no significant associations between the Ser326Cys polymorphism in OGG1 and AD (Coppede et al, 2007; Dorszewska et al, 2009; Parildar-Karpuzoglu et al, 2008), although there are some reports on OGG1 mutations (A53T and A288V) in AD patients (Jacob et al, 2013; Mao et al, 2007). MUTYH, an adenine DNA glycosylase that removes adenine opposite 8-oxodG base pairs (Oka and Nakabeppu, 2011), has also been evaluated and no significant associations between MUTYH and late-onset AD risk identified (Kwiatkowski et al, 2015).…”
Section: Polymorphisms Of Dna Repair Genes In Alzheimer’s Diseasementioning
confidence: 94%